Analisis Spasial pada Kemiskinan di Kabupaten/Kota Provinsi Jawa Tengah Tahun 2011-2017 - Lindung Wicaksono Adha; Maruto Umar Basuki (Universitas Diponegoro, 2020)
This study aims at analyzing the spatial effects and factors that influence poverty in Central Java. The influence of poverty among regions was analyzed by using the moran index to finding spatial autocorrelation of poverty. In regression analysis, this study uses spatial regression in the form of Spatial Autoregressive (SAR). The independent variables used are economic growth, investment, and forming components of HDI. The results indicate that there are spatial autocorrelation through a positive moran index. Furthermore, in the local moran'I analysis, there was a high poverty concentration in the central and southern parts of Central Java province, that are Cilacap, Banyumas, Kebumen, Purworejo, Banjarnegara, Purbalingga, and Wonosobo. Spatial regression analysis shows that spatial variable in this case the poverty of neighboring regions has positive and significant effects. All components forming HDI have a negative effect to poverty levels and only percapita expenditure that is not found significant. meanwhile investment and economic growth has a positive effect even though only investment has a significant effect. This result shows that the investment and economic growth that have been made not reduce poverty well.